PAR1 regulation of CXCL1 expression and neutrophil recruitment to the lung in mice infected with influenza A virus. (19th February 2021) - Antoniak, Silvio; Tatsumi, Kohei; Schmedes, Clare M.; Egnatz, Grant J.; Auriemma, Alyson C.; Bharathi, Vanthana; Stokol, Tracy; Beck, Melinda A.; Griffin, John H.; Palumbo, Joseph S.; Mackman, Nigel
Abstract: Background: Protease‐activated receptor 1 (PAR1) is expressed in various immune cells and in the lung. We showed that PAR1 plays a role in Coxsackievirus B3 infection by enhancing toll‐like receptor 3‐dependent interferon‐ β expression in cardiac fibroblasts. Objectives: We investigated the role of PAR1 in a mouse model of influenza A virus (IAV) infection. Methods: We used mice with either a global deficiency of PAR1, cell type‐specific deficiencies of PAR1, or mutation of PAR1 at the R41 or R46 cleavage sites. Results: PAR1‐deficient mice had increased CXCL1 expression in the lung, increased neutrophil recruitment, increased protein levels in the bronchoalveolar lavage fluid, and increased mortality after IAV infection compared with control mice infected with IAV. Results from mice with cell type‐specific deletion of PAR1 indicated that PAR1 expression by hematopoietic cells suppressed CXCL1 expression, whereas PAR1 expression by endothelial cells enhanced CXCL1 expression in response to IAV infection. PAR1 activation also enhanced polyinosinic:polycytodylic acid induction of interleukin‐8 in a human endothelial cell line. Mutation of the R46 cleavage site of PAR1 was associated with increased CXCL1 expression in the lung in response to IAV infection, which suggested that R46 signaling suppresses CXCL1 expression. Conclusions: These results indicate that PAR1 expression by different cell types and activation by different proteases modulates the immune response during IAV infection.